Comparing the North American Adult Reading Test (NAART) and the Test of Premorbid Functioning (TOPF) to estimate premorbid Wechsler Adult Intelligence Scale - 4th edition FSIQ in a clinical sample with epilepsy. Issue 5 (3rd September 2021) - Reale-Caldwell, AmberRose; Osborn, Katie E.; Soble, Jason R.; Kamper, Joel E.; Rum, Ruba; Schoenberg, Mike R.
Abstract: Estimating premorbid general cognitive functioning is an essential component to the neuropsychological evaluation process. The North American Adult Reading Test (NAART) is a method to predict premorbid general cognitive functioning based on word reading skills developed using the Wechsler Adult Intelligence Scale-Revised (WAIS-R), which is currently in its fourth edition (WAIS-IV). The Test of Premorbid Function (TOPF) was developed using the WAIS-IV, based on the same method as the NAART, to estimate premorbid intellectual ability. There is a paucity of research comparing estimates of premorbid general intellectual ability between the NAART and TOPF. This study evaluated the clinical utility of premorbid estimates of FSIQ derived from the NAART and TOPF in a sample of 101 patients with temporal lobe epilepsy (TLE). Differences between NAART-derived premorbid FSIQs and TOPF simple demographic predicted FSIQs were significant ( p < .001) with large effect sizes. NAART estimated premorbid FSIQ ( M = 104.04, SD = 8.42) was significantly greater than TOPF premorbid estimates ( M = 99.83, SD = 9.26). Results suggested NAART-derived estimates of premorbid FSIQ may be more accurate than TOPF-based estimates, which likely underestimated premorbid FSIQ in this sample of patients with epilepsy. Limitations and future directions are discussed.